Microstructure of Directionally Modified SiC Whisker C/SiC Composites Prepared With LA-CVI Technique - Wang, Jing; Liu, Yongsheng; Wang, Chenhao; Zhang, Yunhai; Li, He; Cheng, Laifei (Frontiers in Materials, 2020)
Poor thermal conductivity of C/SiC composites has become a huge obstacle to be widely used as thermal protection systems and hot structures for hypersonic vehicles. Herein, a high thermal conductivity of C/SiC composites modified with SiC whiskers were constructed by laser assisted chemical vapor infiltration (LA-CVI). The inserted SiC whiskers into the C/SiC composites were served as the second phase, yielding a unique three-dimensional network structure. Density, mechanical properties and thermal conductivity of the prepared composites were systematically investigated. Results show that the bending strength (600 MPa) of the LA-CVI-C/SiC-SiCw composites is 27.6% higher than that of CVI-C/SiC composites (470 MPa). With the fiber debonded, fractured, and pulled out hierarchically, the failure crack propagated express Step-extension. Besides, the thermal conductivity (45.13 Wm-1K-1) of LA-CVI-C/SiC-SiCw composites is a factor 4 to 5 higher than that of CVI-C/SiC composites (10 Wm-1K-1). This work provides not only a facile method to construct high thermal conductivity C/SiC composites, but an effective way to overcome the difficulties of improving the thermal conductivity of CMCs.